Sebaran Geografi Non Polio Enterovirus (NPEV) dari Kasus Layu Akut di Bagian Barat Indonesia 2007-2010 - Pangesti, Krisna N.A.; Susanti1,, Nike; -, Yeremiah (Jurnal Biotek Medisiana Indonesia, 2013)
Acute Flaccid Paralysis (AFP) surveillance which comprises cases and laboratory investigation has been established by WHO in order to achieve the goal of global eradication of polio. NIHRD is one of the national reference polio laboratories in Indonesia that conduct diagnostic test for AFP case specimens from the Western part of Indonesia. AFP cases can be caused by poliovirus and non polio viruses, such as enteroviruses. This recent study investigate the serotype of Non Polio Entero Viruses (NPEV) from AFP cases in 2007-2010 and its geographical distribution. This recent study used biological archieve from AFP cases in 2007-2010. APF specimens was cultured in cell line (RD/L20B) in BSL-2 laboratory. Positive isolates from RD cell lin in negative in L20B cell line in were tested by neutralization test to determine serotype of NPEV. Demography data were also collected from case investigation form of the patients and geographical data was analyzed using GIS arc View 3.3. From a total 2525 AFP cases, 6,8% are NPEV. NPEV cases were mostly found in North Sumater province (20,4%), There is variation fo the number of NPEV cases found each year in 16 province that sen AFP specimens to NIHRD. NPEV cases is commonly found in age group 1-5 years old, (54,3% in 2007, 86,7% in 2008, 62,2% in 2009 and 66,3% in 2010). Serotyping using WHO standard antisera showed that Echovirus is the common serotype found in 2007-2010. However, there were unidentified or untypeable NPEV isolates that need further investigation. NPEV is one of the etiologies that cause Acute Flaccid Paralysis (AFP) in Western part of Indonesia. Further detection of NPEV serotype using molecular tehcnology is needed to reveal other etiologies of AFP.Key words: Acute Flaccid Paralysis, Non Polio Enterovirus, SerotypeÂ AbstrakSurveilans lumpuh layu akut atau Acute Flaccid Paralysis (AFP) yang terdiri dari investigasi kasus dan pemeriksaan laboratorium telah ditetapkan oleh WHO sebagai bagian program pemberantasan polio global. Laboratium Virologi Badan Litbangkes adalah salah satu laboratium rujukan Nasional penyakit polio di Indonesia yang melakukan tes diagnostik untuk spesimen kasus AFP dari Indonesia bagian Barat. Kasus AFP dapat disebabkan oleh virus polio dan virus non polio seperti enterovirus. Tujuan penelitian ini adalah untuk menyelidiki serotipee Non Polio Entero Virus (NPEV) dari kasus AFP pada tahun 2007-2010 dan distribusi geografisnya. Studi ini menggunakan spesimen tersimpan dari kasus AFP pada tahun 2007-2010. Spesimen AFP dikultur dalam lini sel (RD/L20B) di laboratorium BSL-2. Isolat positif dari lini sel RD dan negatif pada lini sel L20B diuji netralisasi untuk menentukan serotipe NPEV. Data denografi juga dikumpulkan dari bentuk kasus investigasi dari pasien sedangkan, data geografis dianalisis menggunakan GIS View 3.3. Dari total 2625 kasus AFP, ditemukan 6,8% kasus NPEV. Kasus NPEV terbanyak ditemukan di provinsi Sumatera Utara (20,4%). Terdapat variasi jumlah kasus NPEV yang ditemukan setiap tahunnya pada 16 provinsi yang mengirim spesimen AFP ke Laboratium Badan Litbangkes. Kasus NPEV umunya ditemukan dalam kelompok usia 1-5 tahun, (54,3% pada tahun 2007, 86,7% pada tahun 2008, 62,2% pada tahun 2009, dan 66,3% pada tahun 2010). Serotyping menggunakan antiserum standar WHO menunjukkan bahwa Echovirus adalah serotipe yang paling banyak ditemukan pada spesimen AFP yang dikumpulkan pada tahun 2007-2010. Namun, terdapat isolat NPEV tidak dikenal atau untypeable yang perlu penyelidikan lebih lanjut. Echovirus merupakan salah satu etiologi yang menyebabkan Acute Flaccid Paralysis (AFP) di Indonesia bagian Barat. Deteksi lebih lanjut serotipe NPEV menggunakan teknologi molekuler diperlukan untuk mengungkapkan etiologi lain dari AFP.Kata Kunci: Acute Flaccid Paralysis, Non Polio Enterovirus,Serotype